Rehabilitative Surgery : A Comprehensive Text for an Emerging Field - Elkwood, Andrew I.; Kaufman, Matthew; Schneider, Lisa F. (Springer International Publishing : Imprint: Springer, 2017)
This book represents the first interdisciplinary text on the emerging field of rehabilitative surgery, in which state of the art procedures from multiple surgical specialties are combined. It proposes a completely new framework for understanding, coordinating, and providing treatment for paralyzed or severely neurologically impaired patients and explains the potentially critical impact of surgery in creating a new baseline of functional status, thereby improving the patient's daily life. Every major aspect of reconstructive surgical treatment is considered, including anesthesia, orthopedic surgery, plastic surgery, neurosurgery, general surgery, vascular surgery, and otolaryngology. The most up-to-date and evidence-based surgeries are clearly described and evaluated, with coverage of treatment of pressure sores, placement of feeding tubes, and upper extremity interventions to improve function and hygiene. Cutting-edge protocols are presented for the surgical treatment of severe nerve injuries, spinal cord injuries, and stroke or cerebrovascular accidents, and a first description and evaluation of phrenic nerve repair to assist weaning of paralyzed patients from ventilators is provided. Both surgical and nonsurgical readers will find this book to be an ideal guide and reference.
Keywords: Medicine.; Neurosurgery.; Orthopedics.; Otorhinolaryngology.; Rehabilitation.; Surgery.; Urology.; elektronické knihy; electronic books